1995
DOI: 10.2307/5648
|View full text |Cite
|
Sign up to set email alerts
|

Selection for the Timing of Great Tit Breeding in Relation to Caterpillar Growth and Temperature

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Ecological Society is collaborating with JSTOR to digitize, preserve and extend access to Journal of Animal Ecology. Summary 1. We investigated the relation between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
323
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 385 publications
(347 citation statements)
references
References 27 publications
(9 reference statements)
10
323
1
Order By: Relevance
“…Temperatures and food supply vary in both non-breeding seasons and at the beginning of breeding. This causes marked variation in survival and local recruitment, mediated by variation in food supply, the timing of breeding and local density (Hochachka et al 1989;Van Noordwijk et al 1995;Visser et al 1998;Both et al 1999;. Such details illustrate the general importance ascribed to environmental variation in determining low (or zero) heritabilities of life-history traits and ¢tness itself (Charlesworth 1987;Price & Schluter 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Temperatures and food supply vary in both non-breeding seasons and at the beginning of breeding. This causes marked variation in survival and local recruitment, mediated by variation in food supply, the timing of breeding and local density (Hochachka et al 1989;Van Noordwijk et al 1995;Visser et al 1998;Both et al 1999;. Such details illustrate the general importance ascribed to environmental variation in determining low (or zero) heritabilities of life-history traits and ¢tness itself (Charlesworth 1987;Price & Schluter 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms through which climate change impacts on biodiversity are varied, but one potentially important mechanism concerns changes in phenology [4]. There is an increasing number of examples now showing changes in the timing of important ecological events, such as flowering in plants and reproduction in animals, in response to climate change [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, expected that temporal changes in foraging behavior among birds in response to the abundance and distribution of arthropods should affect the fitness of individual birds, and hence the structure of the avian community. Although van Noordwijk et al (1995) suggested a relationship between the timing of Great Tit breeding and the availability of Lepidoptera larvae as food for their fledglings, the responses of birds to temporal changes in resource abundance and distribution have been little studied. Further understanding of species-specific responses of birds to temporal changes in resource abundance and distribution in deciduous forests in spring will help to explain the composition of local bird communities (cf.…”
mentioning
confidence: 99%